Archaeological Landscape and Settlement (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
This volume consists of fifteen multidisciplinary papers written by prehistoric, classical, and postclassical archaeologists from different institutions worldwide. They provide quite an open view of different aspects of underway landscape archaeology research in many countries, from Europe to Asia and the Americas. The papers cover a wide variety of territories that, in one way or another, have been crossed, exploited, and changed by the impact of Neanderthals and Modern humans throughout different periods of the Pleistocene and the Holocene. Extreme environments have also been considered, among which are central Asia's desert landscapes and western Europe's northernmost territories. The result consists of an interesting mosaic of papers discussing Medieval, subrecent periods, and archaeometric approaches.